2012
DOI: 10.1063/1.4753973
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and room temperature four-state memory prototype of Sr3Co2Fe24O41 multiferroics

Abstract: Multiferroics exhibit both ferroelectricity and ferromagnetism. The combination of ferroelectricity and ferromagnetism in single phase offers the ability to obtain four physical polarization states, i.e., two electric polarization combined with two magnetic polarization states, achieving four-state memory devices. The four-state memory devices can exponentially increase data storage capacity. In this letter, we synthesized single phase Sr3Co2Fe24O41, which exhibits ferroelectricity, ferromagnetism, and magneto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 30 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…10 Up to now, multiferroic properties have been found in Y-, Z-, M-, and U-type hexaferrites. [11][12][13][14][15][16][17][18][19][20][21][22] Noticeably, large magnetoelectric effects are even observed around room temperature in some M-, U-, and Z-type hexaferrites, which sheds light on the practical applications of magnetoelectric multiferroics. 13,14,17,22 However, to our best knowledge, there are few reports about the multiferroic properties in W-type hexaferrites.…”
mentioning
confidence: 95%
“…10 Up to now, multiferroic properties have been found in Y-, Z-, M-, and U-type hexaferrites. [11][12][13][14][15][16][17][18][19][20][21][22] Noticeably, large magnetoelectric effects are even observed around room temperature in some M-, U-, and Z-type hexaferrites, which sheds light on the practical applications of magnetoelectric multiferroics. 13,14,17,22 However, to our best knowledge, there are few reports about the multiferroic properties in W-type hexaferrites.…”
mentioning
confidence: 95%
“…Although the magnetic and magnetoelectric properties of the Z-type hexaferrites have been intensively studied in the recent years23457891011, only few works have been reported on the dielectric properties of Z-type hexaferrites. The composition dependent dielectric properties of Z-type hexaferrite Ba 3 Co 2 Fe 24 O 41 have been reported121314.…”
mentioning
confidence: 99%
“…7.25) [97]. Other authors have suggested that a four state memory could be achieved with SCZ using two oppositely polarised magnetic and two oppositely polarised electrical states to act as a four state memory [98].…”
Section: Z Ferritesmentioning
confidence: 98%